Analysis of lytic polysaccharide monooxygenase activity in thermophilic fungi by high-performance liquid chromatography–refractive index detector - Yu, Weishuai; Yu, Jie; Li, Duochuan (Frontiers in Microbiology, 2022)
Most current methods for analysing the activity of LPMO are based on the quantification of H2O2, a side product of LPMO; however, these methods cannot assay the LPMO activity of thermophilic fungi because of the low thermostability of H2O2. Therefore, we present a high-performance liquid chromatography–refractive index detector (HPLC-RID) method to assay the LPMO activity of the thermophilic fungus Thermoascus aurantiacus. According to the established method, the specific activities of nTaAA9A C1 and C4 oxidation were successfully analysed and were 0.646 and 0.574 U/mg, respectively. By using these methods, we analyzed the C1 and C4 oxidation activities of the recombinant TaAA9A (rTaAA9A) and mutated rTaAA9A (Y24A, F43A, and Y212A) expressed in Pichia pastoris. The specific activities of rTaAA9A C1 and C4 oxidation were 0.155 and 0.153 U/mg, respectively. The specific activities of Y24A, F43A, and Y212A C1 and C4 oxidation were 0.128 and 0.125 U/mg, 0.194 and 0.192 U/mg, and 0.097 and 0.146 U/mg, respectively. In conclusion, the method can assay the LPMO activity of thermophilic fungi and directly target C1 and C4 oxidation, which provides an effective activity assay method for LPMOs of thermophilic fungi.